Penguatan Islam Wasathiyah melalui Organisasi Lembaga Dakwah Kampus - firman; Prita Indriawati; Basri Basri (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Lembaga Dakwah Kampus as an intra organization which has role for presenting the concept of Islamic Wasathiyah on campus with the aim of expanding Islam and countering radicalism. This research is motivated by students at the Lembaga Dakwah Kampus less of understanding the concept of Wasathiyah even though in practice they generally operate in da 'wah. This research used quantitative method by observation and deep interview. The results of the research show that the Lembaga Dakwah Kampus develops insight not only with regard to Islamic insight but also organizational and leadership development. It is showed that every member has chance to joining the programs (here also provides for non - Muslims regardless of religion, ethnicity. The student movement through the Lembaga Dakwah Kampus provides a solution for campus residents to commit for practicing I slam Wasathiyah with avoiding from certain groups, political interests or radicalism. This concept is necessary to collaborate with various elements of others organizations to develop Islamic insight, character formation, and Islamic culture.